PENGARUH LEVERAGE DAN UKURAN PERUSAHAANTERHADAP PROFITABILITAS PADA PERUSAHAAN SUB-SEKTOR FARMASI PERIODE 2013-2017 - Antonius Mboka; Lukman Cahyono (STIE AUB Surakarta, 2020)
ABSTRACTThis research aims to provide empirical evidence specifically on Leverage and Company Size in predicting profitability. Leverage in this study uses 2 (two) measurements, viz. Debt-to Equity Ratio (DER) and Long-Term Debt-to Equity Ratio (LTDtER) while Profitability uses Return On Asset (ROA) measurement. This type of research is causality with a quantitative approach. This study uses the subject of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. Data analysis methods used multiple linear regression analysis with SPSS for Windows Ver22.00 program through the following stages of this descriptive statistical test, classic assumption test with normality, multicollinearity, heteroscedasticity, and autocorrelation test as soon as a hypothesis test. The results of this research indicate that a partially there is no leverage effect with Debt-to Equity Ratio(DER) proxies and Company Size while there is an effect of Leverage with Long-Term Debt-to Equity Ratio (LTDtER)proxies on the Profitability.Keywords:Leverage, Long-Term Debt-to Equity Ratio, Profitability.